Melatonin may curtail the metabolic syndrome : studies on initial and fully established fructose-induced metabolic syndrome in rats - Cardinali, Daniel Pedro (2013)
Fil: Cardinali, Daniel Pedro. Pontificia Universidad Católica Argentina. Facultad de Medicina. Departamento de Docencia e Investigación; Argentina